E-Learning Strategies For Enhancing Second Language Acquisition In Madrasah Ibtidaiyah - Musyarrafah Sulaiman Kurdi (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to explore the implementation of e-learning strategies for enhancing second language acquisition in Madrasah Ibtidaiyah through a library research approach. The study investigates the key e-learning strategies employed in Madrasah Ibtidaiyah and explores their differences from traditional classroom approaches. It exploress the effectiveness of e-learning in enhancing second language acquisition for students, considering factors such as age, gender, and language proficiency level. Additionally, the role of interactive multimedia tools in supporting second language acquisition and its engagement with students in the learning process is explored. The extent to which e-learning platforms in Madrasah Ibtidaiyah offer personalized learning experiences tailored to individual students' needs and learning styles, and its impact on second language acquisition outcomes are studied. Finally, the challenges faced by teachers in implementing e-learning strategies for second language acquisition and the measures taken to address these challenges effectively are discussed. This research provides valuable insights into the use of e-learning strategies to enhance second language acquisition in Madrasah Ibtidaiyah, offering practical implications for educators and policymakers in the field of language education.